Model Optimasi Perancangan Jaringan Rantai Pasok Biomassa dari Tandan Kosong Kelapa Sawit di Sumatera Barat - Imansuri, Febriza; Hadiguna, Rika Ampuh; Afrinaldi, Feri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
West Sumatra has great potential in developing biomass based on palm oil waste. This is because the largest plantation production in West Sumatra comes from the oil palm commodity of 1,082,820 tons in 2014. Therefore, it is necessary to design a model of supply chain biomass network for the distribution of Empty Fruit Bunches (EFB) from CPO factory suppliers located in West Sumatra and distributed to Depot Pertamina Teluk Kabung. Stages performed in the implementation of this study began with a preliminary study to determine the potential of biomass in West Sumatra. Furthermore, the design of chain supply chain optimization model by identifying supply chain activity, knowing the characteristics of supply chain system and make the formulation of mathematical model. The design of supply chain biomass from Empty Fruit Bunches (EFB) in West Sumatera, starting from raw material Tandan Kosong Kelapa Sawit (TKKS) sourced from Crude Palm Oil (CPO) factory in West Pasaman Regency and surrounding. This is because Pasaman Barat Regency is the central agroindustry of oil palm plantation which has 17 most palm oil factories in West Sumatra. The potential of bioethanol derived from CPO waste can be done by establishing bioethanol plant located with the same CPO factory so that it is adjacent to the source of the raw material. The result of the mathematical model mixed integer linear programming is placement of bioethanol plant location at PT Pasaman Marama Sejahtera with medium scale and total cost of IDR 251,563,700,000.00.